Hipnoterapi untuk Peningkatan Perilaku Personal Hygiene Anak Jalanan - Christina Irnawati; Rahma Widyana (Jurnal Psikologi, 2018)
A city with numerous street children is a big problem. Reducing the number of street children is very difficult and complicated. However, they have to be empowered. In this research one tactic was held to support them. It was to wake up the street children’s personal hygiene behavior. It was because the street children appearance was always dirty and unhealthy. Objective of this research was intervening to those street children with hypnotherapy in order to wake up their personal hygiene behavior. Two street children participated in this experimental research. Their physical cleanliness was categorized as low. The experimental design was the A-B-A-B-A or single case experimental design. This research revealed that the hypnotherapy intervention succeeded to improve subjects’ personal hygiene behavior. Before intervention, their physical cleanliness was categorized as low. The cleanliness scores were 20 and 22 respectively. After receiving hypnotherapy intervention, their cleanliness scores were 40 and 42 respectively (categorized as middle cleanliness level). Those two subjects also reported that they felt physically comfort. It was because their itch skins were cured. This research demonstrated the advantageous of hypnotherapy in getting better subject’s personal hygiene. Key words: Hypnotherapy, Personal Hygiene Behavior, Street Children